Process for removing sulfur dioxide in lepidolite sintering flue gas

Through the double-layer adsorption mechanism of modified nanomaterials and the three-stage temperature control regeneration technology, the problems of low efficiency, high cost and environmental pollution in the removal of sulfur dioxide in the lepidolite sintering flue gas are solved, and an efficient and environmentally friendly desulfurization effect is achieved, which is suitable for the treatment of lepidolite sintering flue gas.

CN120771670APending Publication Date: 2025-10-14YICHUN LITHIUM BATTERY IND RES INST (JIANGXI LITHIUM BATTERY PROD QUALITY SUPERVISION & INSPECTION CENT)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510966396.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-14
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

The existing technology for treating sulfur dioxide in lithium mica sintering flue gas has problems such as low desulfurization efficiency, severe equipment corrosion, high operating costs, wastewater generation and low desulfurizer utilization rate. It is particularly difficult to maintain stable desulfurization performance in high temperature and high humidity environments.

Method used

Modified nanomaterial adsorbents are used, through the double-layer adsorption mechanism of electrostatic agglomeration and bag filter, combined with three-stage temperature control regeneration technology, and a mixture of sodium bicarbonate, slaked lime, lithium sulfate and polyvinylidene chloride fiber is used to prepare the adsorbent for co-coagulation adsorption and regeneration recycling.

Benefits of technology

It achieves efficient removal of sulfur dioxide, with a desulfurization efficiency of 98.3%-99.2%, reduces operating costs by 65%, avoids wastewater discharge, extends equipment life, and improves process stability and economy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120771670A_ABST
    Figure CN120771670A_ABST
Patent Text Reader

Abstract

The invention discloses a process for removing sulfur dioxide in lepidolite sintering flue gas, and belongs to the technical field of modified nano materials. According to the process, sodium bicarbonate (40-65%), slaked lime (15-30%), lithium sulfate (5-12%) and modified polyvinylidene chloride fiber (10-30%) are compounded into an adsorbent, the adsorbent is injected into an electrostatic agglomerator at 120-160 DEG C through high-pressure injection (0.5-1.0 MPa), and the adsorbent and fly ash particles are co-agglomerated under an electric field of 30-40 kV to adsorb SO2. Methyl acrylate / glycidyl methacrylate graft modified nanofibers are innovatively adopted, and a three-section temperature control regeneration technology is combined, so that the adsorbent can be recycled for more than 20 times. The process integrates a dual adsorption mechanism of electrostatic agglomeration and bag filtration, the desulfurization efficiency exceeds 95% in a 10-20% humidity environment, meanwhile, the problems of equipment corrosion of a traditional wet method and low efficiency of a dry method are solved, and the operation cost is reduced by 65% compared with that of a conventional process.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of modified nanomaterials, and in particular relates to a process for removing sulfur dioxide from lithium mica sintering flue gas. BACKGROUND

[0002] Lithium mica is a silicate mineral containing lithium, and due to its rich lithium content, it has become an important raw material in the field of new energy (such as lithium battery manufacturing). In the extraction process of lithium mica, the sintering process is a key step for releasing lithium from the mineral structure. However, this process inevitably produces a large amount of flue gas, with sulfur dioxide being one of the main pollutants. Sulfur dioxide not only causes acid rain and air pollution, but also causes damage to the respiratory system. Therefore, how to efficiently remove SO2 in lithium mica sintering flue gas has become an important issue for the sustainable development of lithium resources.

[0003] Traditional sulfur dioxide removal techniques mainly include wet desulfurization and dry desulfurization. Wet desulfurization (such as limestone-gypsum method) is widely used due to its high desulfurization efficiency, but its disadvantages include equipment corrosion, large amount of wastewater generation, and high operating cost. In contrast, dry desulfurization (such as injection of adsorbent method) is simple to operate and does not produce wastewater, but the utilization rate of desulfurizer is low, and the desulfurization efficiency is difficult to meet the needs of high-concentration SO2 flue gas. These traditional methods face additional challenges when dealing with lithium mica sintering flue gas, as this flue gas has characteristics of high temperature, high humidity, and complex composition.

[0004] In recent years, the development of nanomaterial technology has provided new ideas for gas purification. Modified nanomaterials have shown great potential in SO2 removal due to their high specific surface area, excellent adsorption performance, and adjustable surface chemical properties. For example, through surface modification or doping of transition metals, the adsorption and catalytic conversion capacity of nano-oxides can be significantly improved. Liu et al. (Liu, Y., et al. (2018). Enhanced SO2 adsorption performance of transition metal-modified nano-TiO2. Journal of Hazardous Materials, 350, 1-10.) found that nano-TiO2 loaded with transition metals had a much higher adsorption capacity for SO2 than unmodified materials. In addition, Wang et al. (Wang, X., et al. (2020). High-temperature catalytic removal of SO2 over CeO2 / MgO nanocomposites. Applied Catalysis B: Environmental, 265, 118565.) developed a nano-CeO2 / MgO composite material that can catalyze the conversion of SO2 to sulfate at high temperatures, achieving efficient desulfurization. These studies provide a theoretical basis for the process design of the invention.

[0005] Based on the characteristics of lithium mica sintering flue gas, the invention proposes a sulfur dioxide removal process based on modified nanomaterials, aiming to overcome the limitations of traditional methods, achieve efficient and stable removal of SO2, and reduce environmental load and operating costs. SUMMARY

[0006] The problem to be solved: In the sintering process of lepidolite, the flue gas contains high concentration of sulfur dioxide (SO2), which is harmful to the environment and human health. With the increasing demand for lithium resources in the field of new energy (such as lithium battery manufacturing), the development and utilization of lepidolite has gradually become a research hotspot. However, the existing technology in the treatment of sulfur dioxide in lepidolite sintering flue gas faces many problems and limitations, and an efficient, environmentally friendly and economical technical solution is needed to solve these deficiencies. The invention aims to improve the following specific problems: Wet desulfurization (such as limestone-gypsum method) is currently the commonly used method for SO2 removal in industry, with a desulfurization efficiency of over 90%. However, this method has significant defects when dealing with lepidolite sintering flue gas: Equipment corrosion is serious: The acidic components (such as SO2) in the flue gas react with the aqueous solution used in the wet system to generate sulfuric acid, causing corrosion of the reactor and pipeline, increasing maintenance costs. Waste water generation: Wet desulfurization produces a large amount of wastewater containing sulfate, which requires additional facilities and costs to treat, and if not properly treated, may cause secondary pollution. High operating cost: Wet process requires continuous replenishment of limestone and other raw materials, and disposal of by-products (such as gypsum), making the overall operating cost high. Dry desulfurization (such as injection of adsorbent) has the advantage of simple operation because it does not require water treatment, but it performs poorly in the treatment of lepidolite sintering flue gas: Low utilization rate of desulfurizer: Traditional dry desulfurization uses adsorbents (such as CaO or MgO) with large particles and limited specific surface area, resulting in low contact efficiency with SO2, and the desulfurizer is not fully utilized. Limited desulfurization efficiency: For high-concentration SO2 flue gas, the removal efficiency of dry desulfurization is usually lower than that of wet desulfurization, which cannot meet the strict environmental emission standards. Poor adaptability: The sintering flue gas of lepidolite has the characteristics of high temperature, high humidity and complex composition, and the traditional dry desulfurizer is difficult to maintain stable desulfurization performance in such an environment. Compared with other industrial flue gas, the sintering flue gas of lepidolite has unique physical and chemical properties, bringing additional challenges to existing desulfurization technologies: High temperature and humidity environment: The sintering flue gas temperature is usually between 200-500℃, and the humidity is high, so the traditional desulfurization method either decreases in efficiency or damages the equipment. Complex composition: In addition to SO2, the flue gas may also contain dust, volatile compounds and other acidic gases, increasing the complexity of the desulfurization process. Stability requirement: The existing technology is difficult to continuously and efficiently remove SO2 in such a dynamically changing environment. The desulfurizer currently used (such as limestone or calcium oxide) is mostly a one-time consumable, lacking effective regeneration means, resulting in: Resource waste: The desulfurizer cannot be recycled, increasing raw material consumption. High operating cost: Frequent replacement of desulfurizer makes the process less economical, especially when dealing with large-scale lepidolite sintering flue gas, the cost problem is particularly prominent.To solve the above problems, the present application proposes a sulfur dioxide removal process based on modified nanomaterials, aiming to achieve the following goals: improve desulfurization efficiency: by utilizing the high specific surface area and strong adsorption capacity of modified nanomaterials, ensure efficient removal of SO2 under high temperature and high humidity conditions, desulfurization efficiency can reach more than 95%. Enhance process stability: develop a desulfurizer suitable for the complex composition of lithium mica sintering flue gas, so that it can maintain stable adsorption and catalytic performance in high temperature and high humidity environment. Realize the renewability of desulfurizer: through thermal regeneration or chemical regeneration method, the desulfurizer can be recycled, thereby reducing raw material consumption and operating cost. Avoid secondary pollution: adopt dry desulfurization process, avoid waste water production, reduce environmental load, realize green and environmental protection desulfurization process. Simplify operation and improve economy: design a desulfurization process easy to industrialize, reduce equipment corrosion, improve overall economic benefit. Technical scheme

[0007] To solve the above problems, the present application adopts the following technical scheme.

[0008] A kind of sulfur dioxide removal process in lithium mica sintering flue gas, including the following steps: 40-65 weight parts of sodium bicarbonate, 15-30 weight parts of lime (CAS: 1305-62-0), 5-12 weight parts lithium sulfate and 10-30 weight parts of polyvinyl chloride fiber are mixed uniformly, to obtain adsorbent;Then, the prepared adsorbent is injected into electrostatic agglomerator with temperature of 120-160 ℃, and co-condensation adsorption is carried out with fly ash particles in lithium mica sintering flue gas;Then, the flue gas after co-condensation adsorption is passed into bag filter, and the residual sulfur dioxide is adsorbed;Finally, the adsorbent after co-condensation adsorption is regenerated to obtain regenerated adsorbent for recycling.

[0009] The sulfur dioxide removal process in lithium mica sintering flue gas includes the following steps: 45-60 weight parts of sodium bicarbonate, 20-28 weight parts of lime, 5-12 weight parts of lithium sulfate and 12-25 weight parts of polyvinyl chloride fiber are mixed uniformly, to obtain adsorbent;Then, the prepared adsorbent is injected into electrostatic agglomerator with temperature of 130-150 ℃, and co-condensation adsorption is carried out with fly ash particles in lithium mica sintering flue gas;Then, the flue gas after co-condensation adsorption is passed into bag filter, and the residual sulfur dioxide is adsorbed;Finally, the adsorbent after co-condensation adsorption is regenerated to obtain regenerated adsorbent for recycling.

[0010] The process for removing sulfur dioxide in lithium mica sintering flue gas, comprising the following steps: uniformly mixing 55 parts by weight of sodium bicarbonate, 24 parts by weight of slaked lime, 10 parts by weight of lithium sulfate and 20 parts by weight of polyvinylidene chloride fiber to obtain an adsorbent; then, injecting the prepared adsorbent into an electrostatic agglomerator with a temperature of 140℃ to coagulate and adsorb with fly ash particles in lithium mica sintering flue gas; then, passing the flue gas after coagulation and adsorption into a bag filter to adsorb the residual sulfur dioxide; finally, regenerating the adsorbent after coagulation and adsorption to obtain regenerated adsorbent for recycling.

[0011] The physical and chemical parameters of the polyvinylidene chloride fiber (CAS No. 9002-85-1) are as follows: glass transition temperature: -17℃, melting temperature: 205℃, crystalline density: 1.96g / cm³, fiber diameter: 0.1mm, fiber length: 2mm. The modification method of the polyvinylidene chloride fiber is as follows: disperse the polyvinylidene chloride fiber in 15-30 times its mass of acetone at 60-70℃ and 120-140rpm, then add 2-3 times the mass of the polyvinylidene chloride fiber of methyl acrylate (CAS: 96-33-3) and 0.2-0.7 times the mass of the polyvinylidene chloride fiber of glycidyl methacrylate (CAS: 106-91-2), stir and mix uniformly at 80-90℃ for 24h, then add 0.05-0.15% of the mass of the polyvinylidene chloride fiber of ammonium persulfate, heat to 85±2℃ under nitrogen protection, maintain the stirring rate at 150rpm for 30min, finally, add 0.5-1.2% of the mass of the polyvinylidene chloride fiber of triethylamine (CAS No. 121-44-8), react at 120-140℃ for 2-4h, and obtain after cooling. The coagulation parameters are as follows: the injection method of the adsorbent is high-pressure injection, the pressure of the high-pressure injection is 0.5-1.0MPa, and the pressure source of the high-pressure injection is high-pressure gas. The coagulation parameters are as follows: voltage: 30-40kV, current: 0.1-0.3mA / m 2 , residence time: 1.5-2s. The relative humidity inside the electrostatic agglomerator is 10-20%. The regeneration method is as follows: the temperature of the first section is controlled at 450℃-480℃ for 20-30min; the temperature of the second section is controlled at 500℃-520℃ for 15-20min; the temperature of the third section is controlled at 465℃ for 10-15min.

[0012] For the electrostatic agglomeration system, the core equipment: high-voltage electrostatic agglomerator, working voltage: 30-40 kV (IZS42 series electrostatic eliminator supports ±6 kV voltage), temperature range: 120-160℃, humidity control: 10-20%RH, supporting equipment: SMCIZS42-CG series electrostatic eliminator (double AC mode, maximum load current 100mA). For the bag filter system, model: LFD series multi-bag filter of Lifi Filter, LFD-2-9P type: processing capacity: 270t / h, filter area: 4.5m 2 , suitable pressure: 0.5MPa, frame material: galvanized steel, filter material: glass fiber / activated carbon composite. For the high-pressure injection device, equipment: Graco Finex 289353 type, maximum working pressure: 1.0MPa, nozzle type: air-assisted. For the regeneration heating system: three-stage temperature control regenerator, temperature gradient: 450℃→520℃→465℃, temperature control accuracy: ±5℃, heat source type: electric heating (ZH-65 type steam generator). For monitoring instruments, static electricity detection, IZS31-DF feedback sensor, detection distance: 10-50mm, communication protocol: NPN / PNP output, flow control: Lifi Filter DN200 double filter, interface standard: HG / T20592 flange, pressure rating: PN16.

[0013] Beneficial effects: (1) Significant improvement in desulfurization efficiency: double-layer adsorption mechanism: synergistic effect of electrostatic agglomeration (efficiency >90%) and bag filter (efficiency >95%), total desulfurization efficiency of the system reaches 98.3%-99.2%. Nanofiber modification: PVDC fiber grafted with methyl acrylate increases the specific surface area by 3.2 times, and the SO2 adsorption capacity reaches 135mg / g (traditional CaO adsorbent only 28mg / g).

[0014] (2) Significant reduction in operating costs: regeneration cycle system: three-stage temperature control regeneration technology (450-520℃) allows the adsorbent to be recycled 20-25 times, reducing raw material consumption by 65%-72%; energy optimization: electrostatic agglomerator operates at 140℃ (traditional activated carbon desulfurization requires 130-150℃), reducing energy consumption by 18%.

[0015] (3) Outstanding environmental friendliness: zero wastewater discharge: dry process avoids the generation of acidic wastewater in wet desulfurization (traditional process wastewater treatment cost >8 yuan / ton); by-product resourceization: SO2 concentration >15% (vol) recovered in the regeneration process can be directly used for sulfuric acid production.

[0016] (4) Enhanced process stability: Resistance to complex working conditions: The modified fiber maintains stable adsorption at a humidity of 10-20% (the efficiency of traditional activated carbon decreases by >40% in a high humidity environment); Extended equipment life: FRP fiber pipes (temperature resistance >200°C) replace stainless steel, reducing the corrosion rate by 90%. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a diagram showing the color change of the adsorbent before and after regeneration treatment in Example 5 of the present invention.

[0018] Figure 2 1 is a scanning electron microscope image of the polyvinylidene chloride fiber prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0019] The present invention will be further described below with reference to specific embodiments.

[0020] Unless otherwise defined, the technical and scientific terms used in the following examples have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs. In practical application, the weight parts referred to in the present invention can be set as the unit kilogram. Example

[0021] The invention discloses a process for removing sulfur dioxide from lepidolite sintering flue gas, comprising the following steps: uniformly mixing 405 parts by weight of sodium bicarbonate, 15 parts by weight of slaked lime, 5 parts by weight of lithium sulfate and 10 parts by weight of polyvinylidene chloride fiber to obtain an adsorbent; then, injecting the prepared adsorbent into an electrostatic agglomerator at a temperature of 120°C to perform co-coagulation adsorption on fly ash particles in the lepidolite sintering flue gas; then, passing the flue gas after the co-coagulation adsorption into a bag filter to adsorb residual sulfur dioxide; and finally, regenerating the adsorbent after the co-coagulation adsorption to obtain the regenerated adsorbent for recycling.

[0022] The polyvinylidene chloride fiber has the following physical and chemical parameters: glass transition temperature: -17℃, melting temperature: 205℃, crystallization density: 1.96g / cm3, fiber diameter: 0.1mm, and fiber length: 2mm. The modification method of the polyvinylidene chloride fiber is as follows: the polyvinylidene chloride fiber is dispersed in 15 times the mass of acetone at 60℃ and 120rpm, then 2 times the mass of methyl acrylate and 0.2 times the mass of glycidyl methacrylate are added, and the mixture is stirred and mixed uniformly at 80℃ for 24h, then 0.05% of ammonium persulfate is added, and the temperature is raised to 85±2℃ under nitrogen protection, and the stirring rate is maintained at 150rpm for 30min, finally, 0.5% of triethylamine is added, and the reaction is carried out at 120℃ for 2h, and then cooled to obtain. The parameters of the coagulation are as follows: the injection mode of the adsorbent is high-pressure injection, the pressure of the high-pressure injection is 0.5MPa, and the pressure source of the high-pressure injection is high-pressure gas. The parameters of the coagulation are as follows: voltage: 30kV, current: 0.1mA / m 2 , residence time: 1.5s. The relative humidity inside the electrostatic agglomerator is 10%. The regeneration treatment is as follows: the temperature of the first section is controlled at 450℃ for 20min; the temperature of the second section is controlled at 500℃ for 15min; and the temperature of the third section is controlled at 465℃ for 10min. Embodiment

[0023] A process for removing sulfur dioxide in lithium mica sintering flue gas, comprising the following steps: uniformly mixing 65 parts by weight of sodium bicarbonate, 30 parts by weight of lime, 12 parts by weight of lithium sulfate and 30 parts by weight of polyvinylidene chloride fiber to obtain an adsorbent; then, injecting the prepared adsorbent into an electrostatic agglomerator with a temperature of 160℃ to coagulate and adsorb with fly ash particles in lithium mica sintering flue gas; then, passing the flue gas after coagulation and adsorption into a bag filter to adsorb the residual sulfur dioxide; finally, regenerating the adsorbent after coagulation and adsorption to obtain regenerated adsorbent for recycling.

[0024] The polyvinylidene chloride fiber has the following physical and chemical parameters: glass transition temperature: -17℃, melting temperature: 205℃, crystallization density: 1.96g / cm3, fiber diameter: 0.1mm, and fiber length: 2mm. The modification method of the polyvinylidene chloride fiber is as follows: the polyvinylidene chloride fiber is dispersed in 30 times the mass of acetone at 70℃ and 140rpm, then 3 times the mass of methyl acrylate and 0.7 times the mass of glycidyl methacrylate are added, and the mixture is stirred and mixed uniformly at 90℃ for 24h, then 0.15% of ammonium persulfate is added, and the temperature is raised to 85±2℃ under nitrogen protection, and the stirring rate is maintained at 150rpm for 30min, finally, 1.2% of triethylamine is added, and the reaction is carried out at 140℃ for 4h, and then cooled to obtain. The parameters of the coagulation are as follows: the injection mode of the adsorbent is high-pressure spraying, the pressure of the high-pressure spraying is 1.0MPa, and the pressure source of the high-pressure spraying is high-pressure gas. The parameters of the coagulation are as follows: voltage: 40kV, current: 0.3mA / m 2 , residence time: 2s. The relative humidity inside the electrostatic agglomerator is 20%. The regeneration treatment is as follows: the temperature of the first section is controlled at 480℃ for 30min; the temperature of the second section is controlled at 520℃ for 20min; and the temperature of the third section is controlled at 465℃ for 15min. Embodiment

[0025] A process for removing sulfur dioxide from lithium mica sintering flue gas, comprising the following steps: uniformly mixing 45 parts by weight of sodium bicarbonate, 20 parts by weight of lime, 5 parts by weight of lithium sulfate, and 12 parts by weight of polyvinylidene chloride fiber to obtain an adsorbent; then, injecting the prepared adsorbent into an electrostatic agglomerator with a temperature of 130℃ to coagulate and adsorb with fly ash particles in the lithium mica sintering flue gas; then, passing the flue gas after coagulation and adsorption into a bag filter to adsorb the residual sulfur dioxide; finally, regenerating the adsorbent after coagulation and adsorption to obtain regenerated adsorbent for recycling.

[0026] The physical and chemical parameters of the polyvinylidene chloride fiber are as follows: glass transition temperature: -17℃, melting temperature: 205℃, crystallization density: 1.96g / cm3, fiber diameter: 0.1mm, and fiber length: 2mm. The modification method of the polyvinylidene chloride fiber is as follows: the polyvinylidene chloride fiber is dispersed in 15 times the mass of acetone at 60℃ and 120rpm, then 2 times the mass of methyl acrylate and 0.2 times the mass of glycidyl methacrylate are added, stirring is uniformly carried out at 80℃ for 24h, then 0.05% of ammonium persulfate is added, the temperature is raised to 85±2℃ under nitrogen protection, the stirring rate is maintained at 150rpm for 30min, finally, 0.5% of triethylamine is added, and the reaction is carried out at 120℃ for 2h, and then cooling is carried out to obtain.

[0027] The parameters of the co-condensation are as follows: the injection mode of the adsorbent is high-pressure spraying, the pressure of the high-pressure spraying is 0.5MPa, and the pressure source of the high-pressure spraying is high-pressure gas. The parameters of the co-condensation are as follows: voltage: 30kV, current: 0.1mA / m 2 , residence time: 1.5s. The relative humidity inside the electrostatic agglomerator is 10%. The regeneration treatment is as follows: the temperature of the first section is controlled at 450℃ for 20min; the temperature of the second section is controlled at 500℃ for 15min; and the temperature of the third section is controlled at 465℃ for 10min. Embodiment

[0028] A process for removing sulfur dioxide in lithium mica sintering flue gas, comprising the following steps: uniformly mixing 60 parts by weight of sodium bicarbonate, 28 parts by weight of lime, 12 parts by weight of lithium sulfate and 25 parts by weight of polyvinylidene chloride fiber to obtain an adsorbent; then, injecting the prepared adsorbent into an electrostatic agglomerator with a temperature of 150℃ to co-condense and adsorb with fly ash particles in lithium mica sintering flue gas; then, passing the flue gas after co-condensation and adsorption into a bag filter to adsorb residual sulfur dioxide; finally, regenerating the adsorbent after co-condensation and adsorption to obtain regenerated adsorbent for recycling.

[0029] The physical and chemical parameters of the polyvinylidene chloride fiber are as follows: glass transition temperature: -17℃, melting temperature: 205℃, crystallization density: 1.96g / cm3, fiber diameter: 0.1mm, and fiber length: 2mm. The modification method of the polyvinylidene chloride fiber is as follows: the polyvinylidene chloride fiber is dispersed in 30 times the mass of acetone at 70℃ and 140rpm, then 3 times the mass of methyl acrylate and 0.7 times the mass of glycidyl methacrylate are added, stirring is uniformly carried out at 90℃ for 24h, then 0.15% of ammonium persulfate is added, the temperature is raised to 85±2℃ under nitrogen protection, the stirring rate is maintained at 150rpm for 30min, finally, 1.2% of triethylamine is added, and the reaction is carried out at 140℃ for 4h, and the product is obtained after cooling.

[0030] The parameters of the co-condensation are as follows: the injection mode of the adsorbent is high-pressure spraying, the pressure of the high-pressure spraying is 1.0MPa, and the pressure source of the high-pressure spraying is high-pressure gas. The parameters of the co-condensation are as follows: voltage: 40kV, current: 0.3mA / m 2 , residence time: 2s. The relative humidity inside the electrostatic agglomerator is 20%. The regeneration treatment is as follows: the temperature of the first section is controlled at 480℃ for 30min; the temperature of the second section is controlled at 520℃ for 20min; and the temperature of the third section is controlled at 465℃ for 15min. Embodiment

[0031] The process for removing sulfur dioxide in lithium mica sintering flue gas includes the following steps: 55 parts by weight of sodium bicarbonate, 24 parts by weight of lime, 10 parts by weight of lithium sulfate, and 20 parts by weight of polyvinylidene chloride fiber are uniformly mixed to obtain an adsorbent; then, the prepared adsorbent is injected into an electrostatic agglomerator with a temperature of 140℃, and co-condensation adsorption is carried out with fly ash particles in lithium mica sintering flue gas; then, the flue gas after co-condensation adsorption is introduced into a bag filter to adsorb the residual sulfur dioxide; finally, the adsorbent after co-condensation adsorption is subjected to regeneration treatment to obtain regenerated adsorbent for recycling.

[0032] The physical and chemical parameters of the polyvinylidene chloride fiber are as follows: glass transition temperature: -17℃, melting temperature: 205℃, crystallization density: 1.96g / cm³, fiber diameter: 0.1mm, fiber length: 2mm. The modification method of the polyvinylidene chloride fiber is as follows: the polyvinylidene chloride fiber is dispersed in 24 times of acetone by mass at 65℃ and 130rpm, then 2.5 times of methyl acrylate by mass of the polyvinylidene chloride fiber and 0.5 times of glycidyl methacrylate by mass of the polyvinylidene chloride fiber are added, stirring is uniformly carried out at 85℃ for 24h, then 0.1% of ammonium persulfate by mass of the polyvinylidene chloride fiber is added, the temperature is raised to 85±2℃ under nitrogen protection, the stirring rate is maintained at 150rpm for 30min, finally, 0.8% of triethylamine by mass of the polyvinylidene chloride fiber is added, and the reaction is carried out at 130℃ for 3h, and the product is obtained after cooling.

[0033] The parameters of the coagglomeration are as follows: the injection mode of the adsorbent is high-pressure spraying, the pressure of the high-pressure spraying is 0.8MPa, and the pressure source of the high-pressure spraying is high-pressure gas. The parameters of the coagglomeration are as follows: voltage: 35kV, current: 0.2mA / m 2 , residence time: 1.8s. The relative humidity in the interior of the electrostatic agglomerator is 15%. The mode of the regeneration treatment is as follows: the temperature of the first section is controlled at 470℃ for 25min; the temperature of the second section is controlled at 510℃ for 18min; and the temperature of the third section is controlled at 465℃ for 13min.

[0034] Comparative Example 1 Traditional wet desulfurization: limestone-gypsum desulfurization process is adopted, 20% limestone slurry is used for circulating spraying in the spray tower, the liquid-gas ratio is 15L / m³, and the flue gas is discharged after the temperature is reduced to 50℃ and the demister is used.

[0035] Comparative Example 2 Conventional dry desulfurization: pure calcium oxide powder (200 mesh) is used as the adsorbent, which is sprayed into the 160℃ flue gas through pneumatic conveying, and the electrostatic agglomeration device is not configured. Parameters: Ca / S molar ratio 2.5:1, residence time 2s, and the adsorbent is used once.

[0036] Comparative Example 3 No electrostatic agglomeration process: the adsorbent formula of Example 5 is adopted, but the electrostatic agglomeration device is cancelled, and the bag filter is directly used for treatment. Parameters: spraying pressure 0.5MPa, and the flue gas residence time is shortened to 0.8s.

[0037] Comparative Example 4 Unmodified fiber: Using common polyvinylidene chloride fiber without modification by methyl acrylate, other components are the same as Example 3. Parameters: fiber specific surface area is reduced to 12 m2 / g, glass transition temperature is increased to -5°C.

[0038] Comparative Example 5 Lithium sulfate component is deleted: lithium sulfate in the adsorbent is cancelled, and the mass percentage is adjusted to sodium bicarbonate 60%, slaked lime 30%, polyvinylidene chloride fiber 10%.

[0039] Comparative Example 6 Single-stage regeneration process: using the adsorbent formula of Example 4, but the regeneration treatment is changed to single-stage 520°C for 60 min, without temperature gradient control.

[0040] Comparative Example 7 High-pressure injection overrun: keeping the component ratio of Example 2, the injection pressure is increased to 1.5 MPa.

[0041] Comparative Example 8 Humidity out-of-control condition: canceling humidity control on the basis of the process of Example 1, the flue gas humidity naturally fluctuates.

[0042] Test scheme Flue gas conditions: simulate lithium mica sintering flue gas, SO2 concentration 2000 mg / Nm3, temperature 150°C, humidity 18%. Adsorbent dosage: adsorbent to flue gas mass ratio is 1:1000. Cycle number: after regeneration of the adsorbent, it is used for 20 times, and the desulfurization efficiency decay is evaluated. Running time: each test lasts for 24 h, and the SO2 mass percentage removal rate, adsorbent consumption and energy consumption are recorded.

[0043] Test results: Example 1: desulfurization efficiency: initial 95.2%, after 20 cycles 93.8%. Adsorbent consumption: 0.8 kg per ton of flue gas. Energy consumption: electrostatic agglomeration energy consumption 12 kWh / t of flue gas. Example 2: desulfurization efficiency: initial 98.5%, after 20 cycles 97.2%. Adsorbent consumption: 0.6 kg per ton of flue gas. Energy consumption: electrostatic agglomeration energy consumption 15 kWh / t of flue gas. Example 3: desulfurization efficiency: initial 96.0%, after 20 cycles 94.5%. Adsorbent consumption: 0.75 kg per ton of flue gas. Energy consumption: electrostatic agglomeration energy consumption 13 kWh / t of flue gas. Example 4: desulfurization efficiency: initial 98.0%, after 20 cycles 96.8%. Adsorbent consumption: 0.65 kg per ton of flue gas. Energy consumption: electrostatic agglomeration energy consumption 14 kWh / t of flue gas. Example 5: desulfurization efficiency: initial 99.2%, after 20 cycles 98.3%. Adsorbent consumption: 0.5 kg per ton of flue gas. Energy consumption: electrostatic agglomeration energy consumption 11 kWh / t of flue gas; in addition, as Figure 1The results of the adsorbent treatment are shown. Comparative Example 1: desulfurization efficiency: 92.5%. Operating cost: 12 yuan / t of flue gas treatment cost (including wastewater treatment). Equipment corrosion: annual maintenance cost accounts for 15% of the total cost. Comparative Example 2: desulfurization efficiency: 78.6%. Adsorbent consumption: 2.5 kg / t of flue gas. Energy consumption: no electrostatic agglomeration, low energy consumption but insufficient efficiency. Comparative Example 3: desulfurization efficiency: 85.4%. Adsorbent consumption: 1.2 kg / t of flue gas. Energy consumption: increased pressure drop of bag filter, energy consumption 15 kWh / t of flue gas. Comparative Example 4: desulfurization efficiency: 88.2%. Adsorbent consumption: 1.0 kg / t of flue gas. Circulation performance: efficiency decreased to 75% after 10 cycles. Comparative Example 5: desulfurization efficiency: 90.1%. Adsorbent consumption: 0.9 kg / t of flue gas. Regeneration effect: efficiency decreased to 80% after 15 cycles. Comparative Example 6: desulfurization efficiency: initially 96.5%, decreased to 85% after 10 cycles. Adsorbent consumption: 0.8 kg / t of flue gas. Incomplete regeneration: residual sulfate on the surface of the adsorbent. Comparative Example 7: desulfurization efficiency: 97.0%, but uneven dispersion of adsorbent caused by excessively high injection pressure. Energy consumption: increased energy consumption of injection system by 20%. Comparative Example 8: desulfurization efficiency: decreased to 90% when humidity fluctuates. Adsorbent caking: affects circulation use. Result analysis: analysis of Examples 1-5, desulfurization efficiency is more than 95%, and efficiency attenuation is less than 1.5% after 20 cycles. Example 5 performs best: initial desulfurization efficiency 99.2%, still 98.3% after 20 cycles. Adsorbent consumption is lowest (0.5 kg / t of flue gas), and energy consumption is only 11 kWh / t of flue gas. Optimized ratio, three-stage regeneration and electrostatic agglomeration technology significantly improve efficiency and circulation performance. Analysis of Comparative Examples 1-8, Comparative Example 1 (wet method): efficiency 92.5%, but high cost and serious corrosion. Comparative Example 2 (dry method): efficiency only 78.6%, high adsorbent consumption. Comparative Example 3: efficiency decreased to 85.4% without electrostatic agglomeration, and energy consumption increased. Comparative Example 4: unmodified fiber leads to decreased efficiency and circulation performance. Comparative Example 5: missing lithium sulfate reduces regeneration effect. Comparative Example 6: single-stage regeneration cannot completely restore adsorbent activity. Comparative Example 7: high-pressure injection over-limit increases energy consumption, and effect is not improved. Comparative Example 8: humidity out of control leads to efficiency fluctuation and adsorbent caking. The present application realizes efficient, stable and low-cost SO2 removal through modified nanofiber, electrostatic agglomeration and double adsorption mechanism of bag filter, combined with three-stage temperature-controlled regeneration technology. Compared with traditional methods: desulfurization efficiency is increased to more than 95% (optimum 99.2%). Operating cost is reduced by 65%. Adsorbent can be recycled for more than 20 times. The test results fully demonstrate the significant technical advantages and economic benefits of the present application, which is suitable for lithium mica sintering flue gas treatment scenarios.

[0044] For modified polyvinylidene chloride fibers, during the swelling pretreatment stage, acetone, a polar solvent, osmotically swells the fibers, disrupting the hydrogen bond network between the molecular chains and creating pathways for subsequent monomer penetration. Temperature control in the 60-70°C range accelerates the swelling process while preventing thermal decomposition of the fibers (melting temperature 205°C). Mechanical dispersion at a speed of 120-140 rpm promotes uniform fiber dispersion, resulting in separate, single filaments and an increase in specific surface area to 3.2 times the initial value. Monomer grafting reaction: Grafting mechanism: Under free radical initiation, methyl acrylate monomers bind to free radical sites on the fiber surface by cleaving C=C double bonds, forming long side chains. Effect: The introduction of carboxylate groups (-COOR) enhances SO₂ chemical adsorption. The steric hindrance of the side chains expands the interlayer spacing of the fibers, forming a mesoporous structure (pore diameter 2-5 nm). Glycidyl methacrylate crosslinking and epoxy group activation: The glycidyl methacrylate groups (-O-CH₂-CH(O)CH₂) ring open at high temperatures, forming ether crosslinks with the hydroxyl groups on the fiber surface. Synergistic effect: When the amount of glycidyl methacrylate increases by 0.1 times, the temperature resistance of the fiber increases by 15°C; the cross-linking density is controlled at 3.5×10 - 4 mol / cm³, balancing adsorption capacity and mechanical strength. Ammonium persulfate initiation mechanism: Thermal decomposition characteristics: decomposes at 85°C to produce sulfate radicals, which attack the C-Cl bonds on the fiber surface to generate active sites. Nitrogen protection: oxygen concentration <0.5ppm, ensuring that the average life of free radicals is >30min. Chain growth control: a stirring rate of 150rpm ensures that the monomer conversion rate reaches more than 92%, and the grafting rate is controlled at 35-45%. Triethylamine catalysis, epoxy ring opening: through the nucleophilic attack mechanism, catalyzes the reaction of residual glycidyl ester groups with adjacent carboxylate groups. Network reconstruction: a three-dimensional interpenetrating network structure is formed, and the compressive strength is increased to 18MPa. The porosity is stable in the range of 65-70%, and the BET specific surface area is 320m² / g. At the same time, Example 5 was tested, as shown Figure 2 The scanning electron micrographs shown in the figure show improved thermal stability: the glass transition temperature remains at -17°C, while the thermal decomposition temperature increases from 205°C to 230°C. Adsorption kinetics are optimized: the pseudo-second-order kinetic model fit is R² = 0.996, and the SO2 adsorption capacity reaches 135 mg / g (Langmuir model calculated value is 138 mg / g). Cyclic stability: after 20 regenerations, the specific surface area retention rate is >95%, and the surface functional group decay is <8%. This modification process, through the synergistic effects of physical swelling, chemical grafting, and topological crosslinking, constructs a composite fiber material with a hierarchical porous structure and active adsorption sites, providing an ideal adsorption medium for flue gas desulfurization from lepidolite sintering.

[0045] The above is further detailed description of the present application in combination with the specific embodiments, and cannot be deemed as limitation of the present application to these descriptions. For those skilled in the art of modified nanomaterials, some simple deductions or substitutions can be made without departing from the concept of the present application, and all of them shall be deemed as falling within the protection scope of the present application as defined in the claims.

Claims

1. A process for removing sulfur dioxide from lepidolite sintering flue gas, characterized in that: The following steps are involved: 40-65 parts by weight of sodium bicarbonate, 15-30 parts by weight of slaked lime, 5-12 parts by weight of lithium sulfate and 10-30 parts by weight of polyvinylidene chloride fiber are uniformly mixed to obtain an adsorbent; then, the prepared adsorbent is injected into an electrostatic agglomerator at a temperature of 120-160° C. to perform co-coagulation adsorption on fly ash particles in the flue gas from the lepidolite sintering process; then, the flue gas after the co-coagulation adsorption is passed into a bag filter to adsorb residual sulfur dioxide; finally, the adsorbent after the co-coagulation adsorption is regenerated to obtain the regenerated adsorbent for recycling.

2. The process for removing sulfur dioxide from lepidolite sintering flue gas according to claim 1, wherein: The following steps are involved: 45-60 parts by weight of sodium bicarbonate, 20-28 parts by weight of slaked lime, 5-12 parts by weight of lithium sulfate and 12-25 parts by weight of polyvinylidene chloride fiber are uniformly mixed to obtain an adsorbent; then, the prepared adsorbent is injected into an electrostatic agglomerator at a temperature of 130-150° C. to perform co-coagulation adsorption on fly ash particles in the flue gas from the lepidolite sintering process; then, the flue gas after the co-coagulation adsorption is passed into a bag filter to adsorb residual sulfur dioxide; finally, the adsorbent after the co-coagulation adsorption is regenerated to obtain the regenerated adsorbent for recycling.

3. The process for removing sulfur dioxide from lepidolite sintering flue gas according to claim 2, wherein: The following steps are involved: 55 parts by weight of sodium bicarbonate, 24 parts by weight of slaked lime, 10 parts by weight of lithium sulfate and 20 parts by weight of polyvinylidene chloride fiber are uniformly mixed to obtain an adsorbent; then, the prepared adsorbent is injected into an electrostatic agglomerator at a temperature of 140°C to undergo co-coagulation adsorption with fly ash particles in the flue gas from the lepidolite sintering process; then, the flue gas after the co-coagulation adsorption is passed through a bag filter to adsorb residual sulfur dioxide; finally, the adsorbent after the co-coagulation adsorption is regenerated to obtain a regenerated adsorbent for recycling.

4. The process for removing sulfur dioxide from lepidolite sintering flue gas according to claim 1, wherein: The physical and chemical parameters of the polyvinylidene chloride fiber are as follows: glass transition temperature: -17°C, melting temperature: 205°C, crystal density: 1.96 g / cm³, fiber diameter: 0.1 mm, and fiber length: 2 mm.

5. The process for removing sulfur dioxide from lepidolite sintering flue gas according to claim 1, wherein: The modification method of the polyvinylidene chloride fiber is as follows: the polyvinylidene chloride fiber is dispersed in acetone at 60-70°C and 120-140 rpm, methyl acrylate at 2-3 times the mass of the polyvinylidene chloride fiber and glycidyl methacrylate at 0.2-0.7 times the mass of the polyvinylidene chloride fiber are added, and the mixture is stirred and mixed at 80-90°C for 24 hours. Then, ammonium persulfate at 0.05-0.15% of the mass of the polyvinylidene chloride fiber is added, the temperature is raised to 85±2°C under nitrogen protection, the stirring speed is maintained at 150 rpm for 30 minutes, and finally, triethylamine at 0.5-1.2% of the mass of the polyvinylidene chloride fiber is added, the reaction is carried out at 120-140°C for 2-4 hours, and the mixture is cooled to obtain the obtained product.

6. The process for removing sulfur dioxide from lepidolite sintering flue gas according to claim 1, wherein: The co-coagulation parameters are as follows: the adsorbent is injected by high-pressure injection, the pressure of the high-pressure injection is 0.5-1.0 MPa, and the pressure source of the high-pressure injection is high-pressure gas.

7. The process for removing sulfur dioxide from lepidolite sintering flue gas according to claim 6, characterized in that: The co-coagulation parameters are as follows: voltage: 30-40 kV, current: 0.1-0.3 mA / m 2 , residence time: 1.5-2s.

8. The process for removing sulfur dioxide from lepidolite sintering flue gas according to claim 1, wherein: The internal relative humidity of the electrostatic agglomerator is 10-20%.

9. The process for removing sulfur dioxide from lepidolite sintering flue gas according to claim 1, wherein: The regeneration treatment method is as follows: the temperature of the first stage is controlled at 450℃-480℃, maintained for 20-30 minutes; the temperature of the second stage is controlled at 500℃-520℃, maintained for 15-20 minutes; the temperature of the third stage is controlled at 465℃, maintained for 10-15 minutes.

Citation Information

Patent Citations

  • Sorbent material for removing nitrogen oxides from indoor or cabin air

    CN116322938A

  • Process for removing sulfur dioxide and heavy metal thallium in lepidolite sintering flue gas

    CN116603385A

  • Desulfurization device suitable for coke oven flue gas desulfurization pure dry method

    CN209287035U

  • Graft copolymer preparation process

    RU2202562C2

  • Process for removing SO2 and fly ash from flue gas

    US4960445A